1983
DOI: 10.1111/j.1096-3642.1983.tb01722.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and function of the feeding apparatus in Dermophis mexicanus (Amphibia: Gymnophiona)

Abstract: The morphology and mechanics of feeding in Demophzs mexicanus were studied using descriptive anatomical, cinematographic and electromyographic approaches. The lower jaw has a retroarticular process extending one-third of the total jaw length, and an articulation that restricts anteroposterior movements. Muscles from three anatomically distinct sites, the temporal fossa, the lateral surface of the neck, and the subvertebral region, act to execute the bite during feeding on earthworms. Muscles in the first of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 20 publications
(15 reference statements)
4
102
1
Order By: Relevance
“…Thus, our observations that caecilians frequently use long-axis body rotations when feeding, combined with the fact that these rotations impart significant torques on the head and jaws of the animal, may explain the origin of the unique jaw configuration in derived caecilians (Bemis et al 1983;Nussbaum 1983;O'Reilly 2000;Summers & Wake 2005), which allows them to generate large bite forces with their jaws closed (Summers & Wake 2005). While the reduction of oversized food items remains the most common explanation for long-axis body rotations during feeding, existing data on prey diameter and gape size (Delêtre & Measey 2004) suggest that caecilian prey are rarely oversized.…”
Section: G J Measey and A Herrel Spinning Caeciliansmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, our observations that caecilians frequently use long-axis body rotations when feeding, combined with the fact that these rotations impart significant torques on the head and jaws of the animal, may explain the origin of the unique jaw configuration in derived caecilians (Bemis et al 1983;Nussbaum 1983;O'Reilly 2000;Summers & Wake 2005), which allows them to generate large bite forces with their jaws closed (Summers & Wake 2005). While the reduction of oversized food items remains the most common explanation for long-axis body rotations during feeding, existing data on prey diameter and gape size (Delêtre & Measey 2004) suggest that caecilian prey are rarely oversized.…”
Section: G J Measey and A Herrel Spinning Caeciliansmentioning
confidence: 89%
“…In association with their burrowing habit, most terrestrial species have sturdy, compact skulls, recessed mouths and reduced eyes sometimes covered by the bones of the skull roof. As the head-first burrowing lifestyle of caecilians puts severe constraints on maximal head diameter ( Wake 1993;O'Reilly 2000), the external jaw closer muscles, positioned at the side of the head, are strongly reduced in size in derived caecilians (Bemis et al 1983;Nussbaum 1983;O'Reilly 2000). However, the presence of a mobile quadrate (streptostyly) and a unique jaw-closing system involving the large and well-developed interhyoideus posterior muscle, positioned in line with the head (and thus not increasing the head diameter), suggests that these animals can generate considerable bite forces with the mouth closed (Summers & Wake 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The ventral bending of the skull follows the pattern of cranial kinesis that was previously predicted for caecilians by Iordansky (Iordansky, 1990;Iordansky, 2000). However, although much attention has been paid to the skull roof as an adaptation for burrowing (Peter, 1898;Nussbaum, 1977;Wake and Hanken, 1982;Bemis et al, 1983;Nussbaum, 1983;Wake, 1993), the role of the palate during burrowing has been neglected. Preliminary examination of the nature of the sutures between palatal bones reveals broadly overlapping joints filled by a dense network of collagen fibers, suggesting at least minimal kinesis in this region (H.C.M., personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…Using electromyography, Bemis et al (1983) showed that the IHP acts synergistically with the primary jaw-closing muscles. The jaw-closing function of the IHP has been proposed as an adaptation to a fossorial lifestyle (Nussbaum 1983).…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies of the cranial musculature in caecilians (Wiedersheim 1879;Luther 1914;Lawson 1965;Bemis et al 1983;Nussbaum 1983;Iordanski 1996;Wilkinson & Nussbaum 1997;Kleinteich & Haas 2007) show that the fibre orientation of the IHP in most caecilian species is oblique rather than purely anteroposterior; the muscle fibres run in the caudal and ventral directions. A second simplification in the previous model was to ignore the jaw-closing function of the mm.…”
Section: Introductionmentioning
confidence: 99%